2015
DOI: 10.3390/ijerph120201803
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Seasonal Risk Caused by the Intake of Lead, Mercury and Cadmium through Freshwater Fish Consumption from Urban Water Reservoirs in Arid Areas of Northern Mexico

Abstract: Bioavailability and hence bioaccumulation of heavy metals in fish species depends on seasonal conditions causing different risks levels to human health during the lifetime. Mercury, cadmium and lead contents in fish from Chihuahua (Mexico) water reservoirs have been investigated to assess contamination levels and safety for consumers. Muscle samples of fish were collected across the seasons. Lead and cadmium were analyzed by inductively coupled plasma-optical emission spectrometry, and mercury by cold-vapor at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…However, Pb and Cd had the lowest concentrations in fish muscle (0.4-1 ppb and 3-21 ppb, respectively), as well as Mercury (Hg). Nevárez et al [ 39 ] investigated contamination levels and safety for consumers in fish from Northern Mexico. They found that the provisional tolerable weekly intake (PTWI) suggested by the World Health Organization for methyl mercury (1.6 µg/kg body weight (b.w.)…”
Section: Endocrine Disrupting Chemicals (Edcs)mentioning
confidence: 99%
“…However, Pb and Cd had the lowest concentrations in fish muscle (0.4-1 ppb and 3-21 ppb, respectively), as well as Mercury (Hg). Nevárez et al [ 39 ] investigated contamination levels and safety for consumers in fish from Northern Mexico. They found that the provisional tolerable weekly intake (PTWI) suggested by the World Health Organization for methyl mercury (1.6 µg/kg body weight (b.w.)…”
Section: Endocrine Disrupting Chemicals (Edcs)mentioning
confidence: 99%
“…Chia oil may constitute an available and inexpensive way to provide ALA in higher amounts to the population of many countries characterized by low fish consumption [ 51 , 67 ]. It is not of minor importance considering the actual low availability of fish and the increasing concerns about fish contamination with heavy metals and other toxic products that negatively influence fish consumption [ 68 , 69 ]. Our research has demonstrated that chia oil intake, a natural good source of ALA, allows an important modification in the EPA content of erythrocytes in pregnant mothers and an interesting increase of DHA in their milk.…”
Section: Discussionmentioning
confidence: 99%
“…Lead concentrations in far away from the source decreased with the increase of distance, whereas no significant correlation was found between lead levels in the muscle tissue and the length of both species. [10][11][12][13][14] Other results indicate contamination of these fish foods by lead with mean values varying from 8.0±0.8 to 12.5±1.6 mg kg -1 . The food processing technique accounted for up to seven times increase in fish lead levels.…”
Section: Resultsmentioning
confidence: 99%